Neuroimaging and advanced research techniques may lead to improved outcomes in military members suffering from traumatic brain injury - Moyron, Ron B (Trauma Surg Acute Care Open, 2021)
Recent military conflicts in Iraq and Afghanistan have resulted in the significant increase in blast-related traumatic brain injury (TBI), leading to increased Department of Defense interest in its potential long-term effects ranging from the mildest head injuries termed subconcussive trauma to the most debilitating termed chronic traumatic encephalopathy (CTE). Most patients with mild TBI will recover quickly while others report persistent symptoms called postconcussive syndrome. Repeated concussive and subconcussive head injuries result in neurodegenerative conditions that may hinder the injured for years. Fundamental questions about the nature of these injuries and recovery remain unanswered. Clinically, patients with CTE present with either affective changes or cognitive impairment. Genetically, there have been no clear risk factors identified. The discovery that microglia of the cerebral cortex discharged small extracellular vesicles in the injured and adjacent regions to a TBI may soon shed light on the immediate impact injury mechanisms. The combination of neuroimaging and advanced research techniques may, one day, fill critical knowledge gaps and lead to significant TBI research and treatment advancements.